Investigation of the inhibitory effects of simvastatin in RPMI 2650: an in-vitro study / Jaapar K. H. ... [et al.] - Jaapar, K.H.; Rawi, A.F.; Zuhairi, Z.N.; Sani Gapor, N.A.; Bismelah, N.A.; Mohamed, N.A.H (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Objective: The present study was carried out to investigate the antiproliferative effects of simvastatin involving Human Squamous Nasal Cell Carcinoma (RPMI 2650 cell line), which is one of the most common head and neck cancers with the highest incidence and mortality rates in Asian countries. The anti-cancer effects of simvastatin in NPC have not yet been investigated in depth, hence it will be illustrated in the present study. Materials and methods: The cells were treated with various concentrations of Simvastatin in a dose dependent (0, 0.1, 0. 4, 3.0 mg/ml) and time dependent (24, 48 and 72 hours) manner. The cancer cell viability was then assessed by using MTT assay at absorbance of 590 nm. Results: Simvastatin induced reduction in cell viability number and induced apoptosis in RPMI 2650 cell line. Simvastatin for 72 h significantly reduced cell growth as compared to 48 and 24 h pre-incubation with simvastatin treatment. After 72 h incubation with 0.1 mg/ml, 0.4 mg/ml and 3.0 mg/ml simvastatin, the cell viability decreased from 100% in treated control cells to 23%, 21% and 14% respectively. Conclusions: This finding demonstrate the potential of simvastatin and probably may have therapeutic benefit for NPC cell growth.